2016
DOI: 10.1016/j.otsr.2016.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic bankart surgery: Does gabapentin reduce postoperative pain and opioid consumption? A triple-blinded randomized clinical trial

Abstract: Level I, treatment study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Gabapentin 2 hours preoperatively is recommended to administer because it can achieve the maximum plasma concentration 2-3 h after the injection. Since gabapentin has no hepatic metabolism and is excreted without change through the kidneys, gabapentin is well tolerant [18,41]. In this meta-analysis, gabapentin shows no increase in dizziness, but is associated with the decrease in nausea and vomiting, which may be derived from the reduction of analgesic consumption after the surgery.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Gabapentin 2 hours preoperatively is recommended to administer because it can achieve the maximum plasma concentration 2-3 h after the injection. Since gabapentin has no hepatic metabolism and is excreted without change through the kidneys, gabapentin is well tolerant [18,41]. In this meta-analysis, gabapentin shows no increase in dizziness, but is associated with the decrease in nausea and vomiting, which may be derived from the reduction of analgesic consumption after the surgery.…”
Section: Discussionmentioning
confidence: 90%
“…Among the ve studies included here, two studies report pain scores at 6 h [18,19], three studies report pain scores at 24 h [18][19][20], two studies report analgesic consumption [18,19], four studies report dizziness [18][19][20]26], as well as four studies report nausea and vomiting [18,19,26,27]. Jadad scores of the ve included studies vary from 3 to 5, and all ve studies are considered to be high-quality ones according to quality assessment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have also documented the efficacy of nonopioid oral medications after arthroscopy and other orthopaedic procedures. [12][13][14][15][16][17][18][19] Gimbel et al 14 studied a variety of orthopaedic procedures and concluded that celecoxib may serve as a better option for postoperative pain control compared with hydrocodone/acetaminophen. A recent study by Pham et al 19 showed that use of oral NSAIDs (ibuprofen) and limited narcotics resulted in excellent pain relief and patient satisfaction after arthroscopic meniscectomy, which supports our current findings for limited narcotics after an arthroscopic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of bias summary and risk of bias graph are provided in Figures 2 and 3, respectively. The risk of bias for selective reporting was unclear in 1 study 29 and low in 4 studies. 17,30,31,32 The rest all had low risk of bias.…”
Section: Study Characteristics and Bias Assessmentmentioning
confidence: 99%